Successful Treatment of Surgical Resection, Debridement, and Distraction Osteogenesis in a 22-year-old Female with Chronic Osteomyelitis Femur with Methicillin-resistant Staphylococcus aureus Infection - Grendi Mercy; Denny Adriansyah; Agiona Angeline; Hubertus Corrigan (Biomolecular and Health Science Journal)
Chronic osteomyelitis impedes bone union, requiring immediate management, such as removing the infected bone to aid regeneration. In this case, a 22-year-old woman with a 12 cm bone defect from chronic osteomyelitis had unsuccessful bone healing after three internal fixation surgeries due to persistent infection. To prevent complications, distraction osteogenesis with external fixation was chosen. This method involves applying mechanical strain to stimulate the biological response of damaged tissue, enhancing osteoconductivity and prompting new bone formation with rich blood supply. Despite the scarcity of reports on the effectiveness of this approach for long bone defects caused by osteomyelitis, This case study indicates that distraction osteogenesis using external fixation can be a viable treatment option for bone defects resulting from chronic osteomyelitis.